Penerapan Teori Henry Fayol dalam Program Pembelajaran Bahasa Arab di Pesantren - Utami, Wiwit Nazilah; Mufidah, Nuril; Amrullah, Abdul Malik Karim (Shaut al Arabiyyah, 2025)
The learning process is a series of programs that have been agreed upon and supervised. This certainly requires management in it. One of the management experts, Henry Fayol, defines management in three senses, namely: 1) Management as a process, 2) Management as a collectivity of people who carry out all management activities, 3) Management as an art and as a science. Henry Fayol's management theory focuses more on how management interacts with its personnel. This study will examine how Henry Fayol's theory is applied to the Arabic language learning program in Islamic boarding schools, especially the Firdaus Malang student boarding school. The researcher used a descriptive qualitative method with data collection techniques of observation, interviews, and documentation. In implementing its Arabic language program, the Firdaus student boarding school has applied Henry Fayol's theory based on 14 principles that are the characteristics of Henry Fayol's theory itself. The success of this program management can be seen from the success of the Arabic language program at the Furdaus Islamic boarding school. The success of the Arabic language program at the Firdaus Islamic boarding school can be seen in the alumni who have become Arabic language experts and successful Arabic language teachers in their respective fields. Keyword: Henry Fayol's Management Theory, Learning, Arabic Language Program